Efficacy of tocilizumab treatment in COVID-19 patients with cytokine release syndrome - Erişmiş, Betül; Koçoğlu, Hakan; Ekşi, Fatma; Yeşilbağ, Zuhal; Canbolat Ünlü, Esra; Karandere, Faruk; Yalçın Mutlu, Melek; Icacan, Ozan Cemal; Karabela, Semsi; Hurşitoğlu, Mehmet; Işıksaçan, Nilgün; Kumbasar, Hayat (Journal of Surgery and Medicine, 2021)
Background/Aim: Cytokine release syndrome, a potentially life-threatening condition in SARS‐CoV‐2 (COVID-19) patients, plays a critical role that may lead to the prioritization of tocilizumab (TCZ) in the treatment of this disease. We aimed to present our TCZ-treated SARS‐CoV‐2 patients’ data that might help and guide clinicians in dealing with this infectious disease in their daily practice and research. Methods: This is a retrospective multicenter cohort study from two Turkish pandemic centers. A total of 5165 patients’ data who were hospitalized due to SARS‐CoV‐2 pneumonia from March 16 to May 20, 2020 were screened and 72 patients treated with TCZ were included in the study. We evaluated patients’ demographic data, laboratory and imaging studies, and clinical outcomes and the effect of TCZ treatment on patients’ laboratory and clinical results. Results: O2 saturation levels significantly increased, and fever significantly decreased on the 5th day after TCZ therapy compared to before its initiation (P=0.001, P=0.010, respectively). The decrease in troponin-I, creatinine, LDH, fibrinogen, CRP, procalcitonin, CK, and ferritin levels after TCZ therapy were significant (P<0.05 for all). There was no significant difference in mortality rates with regards to CT results, duration of hospitalization, and the location of initiation of TCZ therapy (clinic vs. ICU) (P>0.05 for all). Importantly, we found a significant increase in mortality rates in patients who received azithromycin, oseltamivir, and ascorbic acid treatments compared to those who did not receive those treatments (P<0.05 for all). Conclusion: Our results showed that TCZ treatment may improve the SpO2 levels, fever and laboratory findings and repress further deterioration of severe SARS-CoV-2 patients. TCZ treatment can be given to the patients in non-ICU clinical beds. It is obvious that randomized controlled studies are needed to observe the efficacy of tocilizumab treatment in COVID-19 patients more clearly.